Muslim-Christian Relations in Damascus amid the 1860 Riot - Abu-Mounes, Rana, author.
1 online resource.
Keywords: On 9 July 1860 CE, an outbreak of violence in the inner-city Christian quarter of Damascus created shock waves locally and internationally. This book provides a step-by-step presentation and reproduction of the facts to assess the true role of all the players and shapers of events. It critically examines the internal and external politico-socio-economic factors involved and argues that economic interests rather than religious fanaticism were the main causes for the riot of 1860. Furthermore, it argues that the riot was not a sudden eruption but rather a planned and organised affair.